The American Turners: their past and present - Annette R. Hofmann (Colégio Brasileiro de Ciências do Esporte, 2015)
The United States has been a nation of immigrants, which is reflected by its multicultural society. Different immigrant groups helped shape the American society through their cultures and traditions. One group was the Germans; they represented a unique and forceful current in the stream of immigration to the United States. In their cultural luggage the German immigrant brought their physical culture to North America, Turnen which was organised in clubs or so-called Turnvereine. The American turner movement has its origin in the mid 19th century, and it is still organised on a national level, since the 1930s under the name American Turners. This article summarises the history of the German-American turner movement until the 1990s, and will also relate to various stages of Americanization within this movement.